Birdsong, speech, and language : exploring the evolution of mind and brain - Bolhuis, Johan J.; Everaert, Martin (MIT Press, 2013)
Scholars have long been captivated by the parallels between birdsong and human speech and language. In this book, leading scholars draw on the latest research to explore what birdsong can tell us about the biology of human speech and language and the consequences for evolutionary biology. They examine the cognitive and neural similarities between birdsong learning and speech and language acquisition, considering vocal imitation, auditory learning, an early vocalization phase ("babbling"), the structural properties of birdsong and human language, and the striking similarities between the neural organization of learning and vocal production in birdsong and human speech. After outlining the basic issues involved in the study of both language and evolution, the contributors compare birdsong and language in terms of acquisition, recursion, and core structural properties, and then examine the neurobiology of song and speech, genomic factors, and the emergence and evolution of language.